Development of new technical solutions design construction machinery reduces the segregation of asphalt mixes - S. V. Saveliev; I. K. Poteryaev; A. B. Letopolski; V. V. Miheev (Вестник СибАДИ)
In this paper the influence of transport on the environment temperature asphalt mix segregation. The experimental and statistical studies in the construction of asphalt pavement in the Republic of Altai. On the basis of studies to determine the temperature and volume of asphalt mix during transportation to a distance of 34 km. Developed technical solution design of the machine to reduce the segregation of asphalt mixture.